Implementasi Metode Backward Chaining Dalam Mendiagnosis Penyakit Periodontitis Terhadap Perokok Aktif Berbasis Android - Muhammad Agri Febriansyah; Ilham Faisal; Divi Handoko (DPPM Universitas Pelita Bangsa, 2023)
Periodontitis is a serious dental and oral health problem, especially for individuals who are involved in smoking habits. This study discusses the implementation of the backward chaining method in diagnosing periodontitis in active smokers using the Android platform. The backward chaining method is used as an approach in expert systems to analyze symptoms and risk factors associated with periodontitis. The system implemented on the Android platform allows users to access it easily via mobile devices. The results of this study are expected to help active smokers receive early information about the possibility of periodontitis and encourage them to seek further treatment from medical professionals. With this application, it is hoped that awareness about dental and oral health and the impact of smoking on periodontitis can increase among active smokers